Pharmacogenetics of pediatric acute lymphoblastic leukemia in Uruguay: adverse events related to induction phase drugs - Burgueño-Rodríguez, Gabriela; Méndez, Yessika; Olano, Natalia; Schelotto, Magdalena; Castillo, Luis; Soler, Ana María; da Luz, Julio (Frontiers in Pharmacology, 2023)
In Uruguay, pediatric acute lymphoblastic leukemia cure rate is 82.2%, similar to the ones reported in developed countries. However, many patients suffer adverse effects that could be attributed, in part, to genetic variability. This study aims to identify genetic variants related to drugs administered during the induction phase and to analyze their contribution to adverse effects, considering individual genetic ancestry. Ten polymorphisms in five genes (ABCB1, CYP3A5, CEP72, ASNS, and GRIA1) related to prednisone, vincristine, and L-Asparaginase were genotyped in 200 patients. Ancestry was determined by 45 Ancestry Informative Markers. The sample ancestry was 69.2% European, 20.1% Native American, and 10.7% African, but with high heterogeneity. Mucositis, Cushing syndrome, and neurotoxicity were the only adverse effects linked with genetic variants and ancestry. Mucositis was significantly associated with ASNS (rs3832526; 3R/3R vs 2R carriers; OR: = 6.88 [1.88-25.14], p=0.004) and CYP3A5 (nonexpressors vs expressors; OR: 4.55 [1.01-20.15], p=0.049) genes. Regarding Cushing syndrome, patients with the TA genotype (rs1049674, ASNS) had a higher risk of developing Cushing than those with the TT genotype (OR: 2.60 [1.23-5.51], p=0.012). Neurotoxicity was significantly associated with ABCB1 (rs9282564; TC vs TT; ], p=0.007). Moreover, patients with <20% Native American ancestry had a lower risk of developing neurotoxicity than those with ≥20% (OR: 0.312 [0.120-0.812], p=0.017). This study shows the importance of knowing individual genetics to improve the efficacy and safety of acute lymphoblastic leukemia.